2001
DOI: 10.1200/jco.2001.19.4.1207
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Circulating Angiogenic Factors in Cancer Patients

Abstract: Circulating VEGF seems to be a reliable surrogate marker of angiogenic activity and tumor progression in cancer patients. Evaluation of circulating angiogenic factors is a promising novel approach of prognostication in cancer patients that has the advantages of being convenient and noninvasive, and it may provide new prognostic information that is not afforded by conventional clinicopathologic prognostic indicators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
372
0
15

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(398 citation statements)
references
References 153 publications
11
372
0
15
Order By: Relevance
“…The results showed that patients with high intratumoral level of VEGFR2 were more prone to develop distant metastases, and had an impaired survival. A huge amount of publications have shown higher expression of the ligand, VEGF to be correlated with shorter survival times in several tumor types including breast cancer [23]. VEGFR2 is less studied and the data concerning the prognostic and predictive role contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that patients with high intratumoral level of VEGFR2 were more prone to develop distant metastases, and had an impaired survival. A huge amount of publications have shown higher expression of the ligand, VEGF to be correlated with shorter survival times in several tumor types including breast cancer [23]. VEGFR2 is less studied and the data concerning the prognostic and predictive role contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…However, no association between increased serum levels of FGF2 and tumor type was observed in later studies on a large spectrum of metastatic carcinomas even though two-thirds of the patients showing progressive disease had increasing serum levels of the angiogenic factor compared with less than onetenth of the patients showing response to therapy [200]. The clinical significance of circulating FGF2 in individual types of cancer has been recently reviewed [201]. Briefly, the levels of circulating FGF2 may have prognostic significance in head and neck cancer, lymphoma, leukemia, prostate carcinoma, and soft tissue sarcoma but they do not correlate with breast cancer progression and their significance in colorectal carcinoma is unclear.…”
Section: Human Tumorsmentioning
confidence: 99%
“…Additional biological parameters are therefore required to gain more accurate insight into the outcome of metastatic breast cancer patients. Recent cancer research has highlighted the importance of tumour neovascularisation in the initial and metastatic growth of cancer (Hanahan and Folkman, 1996) and there is solid evidence supporting the evaluation of tumour angiogenesis for prognosis in cancer patients (Poon et al, 2001). Thus, the assessment of angiogenic factor production may allow a better estimation of survival for patients with metastatic breast cancer.…”
mentioning
confidence: 99%
“…Elevated serum levels of VEGF have been found in metastatic cancer patients. These levels have been correlated to the clinical course of the disease in several tumour types (Poon et al, 2001;Ugurel et al, 2001;Molica et al, 2002). As most serum VEGF is released from platelets during blood clotting, it has been suggested that plasma VEGF may be a better reflection of ongoing angiogenic activity, although this assumption has been challenged (Banks et al, 1998;Salven et al, 1999a;Wynendaele et al, 1999;George et al, 2000).…”
mentioning
confidence: 99%